Effect of M-Learning on promoting the awareness of faculty members of the universities of medical sciences of Iran about their employment regulations in 2020 - Gilavand, Abdolreza (Frontiers in Public Health, 2022)
Introduction: New technologies enable universities to incorporate innovative teaching-learning strategies into their curricula. Therefore, this research investigates the effect of M-Learning on promoting the awareness of faculty members of the universities of medical sciences of Iran about their employment regulations. Materials and Methods: The statistical population of this research included all faculty members of Ahvaz Jundishapur University of Medical Sciences in southwestern Iran. 114 people entered the quasi-experimental study through sampling at convenience. First, we sent the designed mobile app to them through social networks to install on their phone. We measured their knowledge and views about the app and M-Learning through a researcher-construed questionnaire. Results: M-Learning and App was able to increase the awareness of faculty members, which was significant according to their academic rank and work experience. Faculty members who were professor and instructor, as well as those who were experience under 5 years or 11 to 20 years of experience had gained more knowledge (P = 0.00). It was not significant in other variables. 98% of the faculty members considered the technical capabilities of the designed app appropriate. 97% of the faculty members suggested M-Learning for teaching similar subjects in their profession. Discussion and Conclusion: The faculty members had a positive attitude towards this designed educational app and M-Learning. Designing similar mobile training apps can improve their professional performance.